Common mental disorders in hematopoietic stem cell transplant patients: a scoping review - Ana Clara Paiva de Almeida; Valéria Dantas de Azevedo; Tássia Regine de Morais Alves; Viviane Euzébia Pereira Santos; Glauber Weder dos Santos Silva; Isabelle Campos de Azevedo (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to map common recurrent mental disorders in patients undergoing hematopoietic stem cell transplantation. Methods: this is a scoping review carried out in January 2022 in electronic databases and repositories of dissertations and thesis. Studies that answered the research question, met the objective of the study and were available in full electronically, in any language, were included. Results: the sample consisted of 28 studies, 14 of which were published in the United States of America. The common mental disorders found were depressive, anxiety, post-traumatic stress and mood disorders. Twenty symptoms were mentioned, among the most prevalent are fatigue and sleep disorders/insomnia. Conclusions: the difficulty and importance of carrying out the differential diagnosis of these disorders were highlighted, since their symptoms can be confused with other health problems and have a strong potential to interfere with patients' evolution.